235k views
0 votes
Which is equivalent

Which is equivalent-example-1
User Fanlix
by
5.3k points

2 Answers

7 votes

Answer:

D

Explanation:

Using the rules of exponents


a^(-m)
(1)/(a^(m) )


a^{(1)/(2) }
√(a)

Hence


36^{-(1)/(2) } =
\frac{1}{36^{(1)/(2) } } =
(1)/(√(36) ) =
(1)/(6)

User Sphoenix
by
4.7k points
4 votes

For this case we must find an expression equivalent to:


36 ^ {- \frac {1} {2}}

By definition of power properties we have to:


a ^ {- 1} = \frac {1} {a ^ 1} = \frac {1} {a}

So, rewriting the expression we have:


\frac {1} {36 ^ {\frac {1} {2}}}=

By definition of power properties we have to:


\sqrt [n] {a ^ m} = a ^ {\frac {m} {n}}

So:


\frac {1} {\sqrt {36}} =\\\frac {1} {\sqrt {6 ^ 2}} =\\\frac {1} {6}

Answer:

Option D

User PatrickJ
by
5.2k points